USING ONLINE PEER REVIEW AS A STRATEGY TO IMPROVE WRITING SKILLS - Ula, Erfa Navadiatul (Sanata Dharma University Yogyakarta, 2022)
This research investigated the use of online peer review as a strategy to improve writing skills in the revision process. This qualitative study will recruit two peers of a private university in Malang based on two criteria 1) they have passed an academic writing course with an excellent score, and 2) they were students who use online media to conduct peer reviews. Using a semi-structured interview, the students were asked what types of online resources they use for online peer review, and how they do peer review online. The interview data will be analyzed using content analysis to triangulate the data, investigator triangulation will be performed by involving two data analysts. The result of the study was students used WhatsApp and Zoom media to conduct online peer review, and students provide their writing in the form of an online file to the peer for review about grammar, writing effectiveness, and diction errors with several platforms, such as grammar checkers and online dictionaries to assist the revision process.